Unraveling the Shift to the Entrepreneurial Economy - D.B. Audretsch; A.R. Thurik (Tinbergen Institute, 2010)
A recent literature has emerged providing compelling evidence that a major shift in the organization of the developed economies has been taking place: away from what has been characterized as the managed economy towards the entrepreneurial economy. In particular, the empirical evidence provides consistent support that (1) the role of entrepreneurship has significantly increased, and (2) a positive relationship exists between entrepreneurial activity and economic performance. However, the factors underlying this observed shift have not been identified in a systematic manner. The purpose of this paper is to suggest some of the factors leading to this shift and implications for public policy. In particular, we find that a fundamental catalyst underlying the shift from the managed to the entrepreneurial economy involved the role of technological change. However, we also find that it was not just technological change but rather involved a number of supporting factors, ranging from the demise of the communist system, increased globalization, new competition for multinational firms and higher levels of prosperity. Recognition of the causes of the shift from the managed to the entrepreneurial economy suggests a rethinking of the public policy approach. Rather than the focus of directly and exclusively on promoting startups and SMEs, it may be that the current approach to entrepreneurship policy is misguided. The priority should not be on entrepreneurship policy but rather a more pervasive and encompassing approach, policy consistent with an entrepreneurial economy.
Keywords: E10; E60; H11; L1; L2; M13; O10; 330; entrepreneurship; economic regime switch; economic policy; new firms and startups; economic development; firm performance and market structure; globalization; new technologies; Unternehmer; Technischer Fortschritt; Systemtransformation; Wirtschaftsordnung; Welt